Narrow-chirality distributed single-walled carbon nanotube synthesis by remote plasma enhanced ethanol deposition on cobalt incorporated MCM-41 catalyst - Si, Rongmei (2014)
We demonstrated the synthesis of single-walled carbon nanotubes (SWCNTs) with narrow chiral distribution on cobalt incorporated MCM-41 catalyst using ethanol as carbon feedstock by remote plasma enhanced chemical vapor deposition. The use of remote plasma enables the decomposition of the nontoxic ethanol to occur away from the site of SWCNT growth. This allows separate manipulation of carbon radical generation and SWCNT growth. A series of syntheses were carried out at plasma power from 0 to 250 W and growth temperature from 625 to 875 oC. Results have revealed that the plasma power and growth temperature affect carbon radical generation and recombination, as well as the reduction and nucleation of cobalt species. In addition, the remote ethanol plasma etching does not damage the grown SWCNTs. The chirality of resulting SWCNTs shows minor changes under different plasma power. On the other hand, the diameter of SWCNTs can be adjusted (from 0.7 to 1 nm) by changing the growth temperature. At the optimum condition of 200 W plasma power and 775 oC growth temperature, (7,5) and (8,4) nanotubes account for more than 50% of all semiconducting nanotube species. These results demonstrate the potential of utilizing plasma process in chiral selective growth of SWCNTs.